Analysis of business processes in electronic content-commerce systems - Vysotska, V.; Chyrun, L.; Kozlov, P. (Commission of Motorization and Energetics in Agriculture, 2016)
Practical factor of information resources processing in electronic content commerce systems (ECCS) is related to solving problems with increase in content amount on Internet, active development of e-business, rapidly spreading Internet accessibility, information products and services extension set, increasing demand for content. The aim was to developmethods and software of information resources processing to improve the efficiency of ECCS due to increased sales of content. Article is devoted to the standardized methods and software development of information resources processing in ECCS. In this paper an actual scientific problem of development and research in methods and means of information resources processing ECCS was solved with use of designed classification, mathematical providing and software and generalized ECCS architecture. ECCS classification was researched and improved on the basis of analyzing and evaluating of such systems. It made possible to determine, detail and justify choice of their functional possibilities for content lifecycle designing. The task of developing methods and software formation, management and support of information products resolved with a theoretically grounded concept by automating information resources processing in ECCS to increase content selling for constant user, by involvement of potential users and expanding the boundaries of the target audience.
Keywords: information resources; content; content lifecycle; electronic content commerce system